PERTANGGUNG JAWABAN PIDANA ANAK DI BAWAH UMUR MENURUT HUKUM ISLAM - Nufiar Nufiar (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
Islam upholds the public interest compared to personal interests. In otherwords, the community must take precedence, not the other way around. Thereforeany criminal act that disturbs order and peace of the people is considered as acrime against Allah because crime or criminal acts are something that isprohibited by the Shari'a. In Islamic law, the punishment is given to give adeterrent effect to my guard to realize not to do it again. What's interesting aboutpunishment in Islam as a form of healing, practical, economical and accountable.So in Islamic Law, criminal acts (jarimah) are Syara's bans which are punishable.The prohibition is also sometimes in the form of an act that is prevented, or leavesthat is told. With the mention of syara 'words, it is intended that the prohibitionsmust come from provisions (nasas) syara' and whether or not to do a new act isconsidered as jarimah, if it is punishable by it. Because the commandments andprohibitions come from Syara 'then the commands and prohibitions are onlydirected at people who are of sound mind and can understand the imposition(taklif). Because, in the tradition of Islamic law, the imposition means the call(khithab), and people who cannot understand, such as animals and inanimateobjects, cannot be the object of the Bible. Therefore a sentence will be applied if itfulfills the elements set out in Islamic criminal law.